The Unfolding of Cognitive Effort During Sentence Processing: Pupillometric Evidence From People With and Without Aphasia - Chapman, Laura Roche; Hallowell, Brooke (Journal of speech, language, and hearing research, 2021)
Purpose: Arousal and cognitive effort are relevant yet often overlooked components of attention during language processing. Pupillometry can be used to provide a psychophysiological index of arousal and cognitive effort. Given that much is unknown regarding the relationship between cognition and language deficits seen in people with aphasia (PWA), pupillometry may be uniquely suited to explore those relationships. The purpose of this study was to examine arousal and the time course of the allocation of cognitive effort related to sentence processing in people with and without aphasia. Method: Nineteen PWA and age- and education-matched control participants listened to relatively easy (subject-relative) and relatively difficult (object-relative) sentences and were required to answer occasional comprehension questions. Tonic and phasic pupillary responses were used to index arousal and the unfolding of cognitive effort, respectively, while sentences were processed. Group differences in tonic and phasic responses were examined. Results: Group differences were observed for both tonic and phasic responses. PWA exhibited greater overall arousal throughout the task compared with controls, as evidenced by larger tonic pupil responses. Controls exhibited more effort (greater phasic responses) for difficult compared with easy sentences; PWA did not. Group differences in phasic responses were apparent during end-of-sentence and postsentence time windows. Conclusions: Results indicate that the attentional state of PWA in this study was not consistently supportive of adequate task engagement. PWA in our sample may have relatively limited attentional capacity or may have challenges with allocating existing capacity in ways that support adequate task engagement and performance. This work adds to the body of evidence supporting the validity of pupillometric tasks for the study of aphasia and contributes to a better understanding of the nature of language deficits in aphasia.